THE INFLUENCE OF SCHOOL ENVIRONMENT AND ENTREPRENEURSHIP EDUCATION PROGRAMME ON STUDENTS' ENTREPRENEURIAL CHARACTER IN SCHOOL WITH MOTIVATION AS MEDIATION - Robertus Dri Harnanto; Rudy C Tarumingkeng (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2025)
The entrepreneurial character of students at the Senior High School (SMA) and Vocational High School (SMK) levels is influenced by many things. The learning carried out in SMA is different from the learning carried out in SMK. Vocational High Schools implement entrepreneurship education designed as an integral part of the vocational curriculum oriented towards the world of work and entrepreneurship while in general High Schools, entrepreneurship education is not a major part of the national curriculum structure, but is more often present in the form of extracurricular activities, local content, or thematic and project-based Pancasila (P5) student profile strengthening programmes. This quantitative study was conducted to examine the effect of school environment and entrepreneurship education on the entrepreneurial character of students at school with motivation as mediation. The sample used is class XI and XII students totalling 100 students in one of the private high schools in Kota Jababeka Cikarang which organises entrepreneurship education programmes in schools. Data collection was carried out through a tool in the form of a questionnaire, which consisted of 20 statements using a Likert scale with a scale of 1 - 5 to facilitate respondents in providing an assessment of each statement. Data analysis technique used in this research is using Smart Partial Least Square (SmartPLS). SmartPLS is a tool used for data analysis with the Structural Equation Modeling (SEM) method, which allows researchers to evaluate the relationship between latent variables and their indicators. The results showed that entrepreneurship education implemented in high schools had a significant positive effect on students' entrepreneurial motivation and character. The school environment exerts a significant but small-scale positive influence in building motivation to foster entrepreneurial character. The findings imply that investment in a well-designed entrepreneurship programme can generate positive impact in preparing individuals with strong entrepreneurial character.